Coronary atherosclerosis within a myocardial bridge, not a benign condition. Issue 1 (1st July 1998) - de Winter, Robbert J; Kok, Wouter E M; Piek, Jan J
Abstract : In patients with myocardial bridging, the area within the bridge usually remains free from atherosclerotic disease. The case of a 47 year old man is described who had the rare combination of myocardial bridging with an atherosclerotic plaque within the area of bridging, which was detected with intravascular ultrasound but not with coronary angiography. The clinical history of the patient demonstrates that this is not a benign condition. In symptomatic patients the bridged segment should be screened for the presence of plaque with intracoronary ultrasound.